BIOLOGICAL ACTIVITY OF GUANDU BEAN (Cajanus cajan (L.) Millsp.) AND ITS POSSIBILITY OF USE AS A SUPPLEMENTATIVE METHOD OF BREWERWORT - Leonardo Oliveira Lima, Felicson; Brandão Mafra de Carvalho, Giovani (Revista Interface Tecnológica, 2023)
The bean guandu (Cajanus cajan (L.) Millsp.) is a legume that belongs to the Fabaceae family, commonly grown in Northeast Brazil and other tropical countries. It has several biological activities, being used in traditional medicine, fertilization, and animal feeding. Regarding beer production, this can be mediated through the inclusion of various sources of carbohydrates, called brewing adjuncts. In view of the above and knowing the biological potential of Cajanus cajan, the present study aimed to describe the main biological activities of the cowpea and some of its therapeutic applications, besides suggesting its use as a brewing adjunct. This is a systematic review, with qualitative character, mediated through the parameters established by PRISMA, which after applying the inclusion and exclusion criteria, a total of 54 articles were obtained, these, published between the years 2010 to 2022. It is concluded that through the bioactive composition of the cowpea, it can be a good alternative for use as a brewing adjunct, being able to use the beverage, in addition to its economic and ecological benefits, various therapeutic effects in addition to improvements in its sensory and acceptability aspects.